RECORDS OF PREDATORS AND PARASITES (VERTEBRATES AND INVERTEBRATES) OF CREOSOTE BUSH GRASSHOPPER BOOTETTIX ARGENTATUS BRUNER, 1889, (ORTHOPTERA: ACRIDIDAE: GOMPHOCERINAE) FROM THE BOLSÓN DE MAPIMI, DGO. (CHIHUAHUAN DESERT), MEXICO - Rivera García, Eduardo (Instituto de Ecología, A.C., 2022)
This paper summarizes unpublished information and isolated field observation records on the principal predators (9 vertebrates, 10 insect and 2 orb weaver and a terrestrial spider species) and parasites (an insect and one mite species) of B. argentatus a non economic, highly specialized monophagous grasshopper species of creosote bushes Larrea tridentata in Mapimi Biosphere Reserve, a southern region of the Chihuahuan Desert.